2004
DOI: 10.1159/000074840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E and Vitamin C Supplementation on Antioxidative State and Renal Glomerular Basement Membrane Thickness in Diabetic Kidney

Abstract: The aim of this study was to analyze the effect of vitamins C and E on malondialdehyde (MDA) content and activities of key antioxidant enzymes: superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) as well as glomerular basement membrane (GBM) thickness in streptozotocin-induced diabetic kidney in rats. Wistar male rats were divided into following groups (12 rats each): the control, diabetic rats, diabetic rats whose drinking water was supplemented with vitamin C in a dose of 1.0 g/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
59
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 16 publications
9
59
3
2
Order By: Relevance
“…As regard to study the effect of vitamin E treatment on HFD induced oxidative stress. As our study showed that treatment with vitamin E for 8weeks didn't result in significant change in the body weight of the antioxidant group (group IV) compared to the positive control group (group IIb) as showed in (table 2) .This is in agreement with Kedziora-Kornatowska et al, [47] as they revealed that administration of vitamins C and E did not affect body weight of diabetic rats. However, in the same group, the insulin resistance was significantly improved manifested by significant decrease (p <0.05) in serum glucose levels, HOMA-IR (p <0.05 ) and decrease in serum insulin level(although statistically nonsignificant) as showed in (table 2),and these results are in agreement with Manning et al [48] as they reported that vitamin E improved insulin sensitivity and the associated features of insulin resistance in overweight individuals and they explained that the mechanisms of the improvement in insulin resistance were by decreasing cellular oxidative stress, altering membrane properties, and decreasing inflammatory activity.…”
Section: Discussionsupporting
confidence: 91%
“…As regard to study the effect of vitamin E treatment on HFD induced oxidative stress. As our study showed that treatment with vitamin E for 8weeks didn't result in significant change in the body weight of the antioxidant group (group IV) compared to the positive control group (group IIb) as showed in (table 2) .This is in agreement with Kedziora-Kornatowska et al, [47] as they revealed that administration of vitamins C and E did not affect body weight of diabetic rats. However, in the same group, the insulin resistance was significantly improved manifested by significant decrease (p <0.05) in serum glucose levels, HOMA-IR (p <0.05 ) and decrease in serum insulin level(although statistically nonsignificant) as showed in (table 2),and these results are in agreement with Manning et al [48] as they reported that vitamin E improved insulin sensitivity and the associated features of insulin resistance in overweight individuals and they explained that the mechanisms of the improvement in insulin resistance were by decreasing cellular oxidative stress, altering membrane properties, and decreasing inflammatory activity.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of excessive oxidative stress in the glomeruli of diabetic rats is implicated in the mesangial expression of the extracellular matrix and renal dysfunction, such as increased glomerular filtration, albuminuria, and glomerulosclerosis (14,28,29). Moreover, increased urinary albumin excretion and tissue 8-OHdG in the kidney were observed simultaneously in the STZ-diabetic rats (26).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a combination of vitamins E and C administered for 12 weeks decreased lipid peroxidation and augmented the activities of antioxidant enzymes in the kidneys of stretozotocin diabetic rats. The treatment also reduced urinary albumin excretion, decreased kidney weight and reduced the thickness of the glomerular basement membrane [187]. Tocotrienol, a component of vitamin E that may accumulate more effectively in membranes than α-tocopherol [188], was shown to ameliorate experimental nephropathy in STZ-diabetic rats [189].…”
Section: Other Anti-glycative Compoudsmentioning
confidence: 96%